Peningkatan Produksi dan Mutu Benih Kedelai Varietas Hitam Unggul Nasional Sebagai Fungsi Jarak Tanam dan Pemberian Dosis Pupuk P. - Harun Rasyid (Jurnal Gamma, 2013)
Peningkatan Produksi dan Mutu Benih Kedelai Varietas Hitam Unggul Nasional Sebagai Fungsi Jarak Tanam dan Pemberian Dosis Pupuk P.Improved Seed Production and Quality of Soybean Varieties Black National Excellence In Distance Function Planting Fertilizer Dosage and Administration P.Harun RasyidJurusan Agroteknologi, Fakultas Peternakan PertanianUniversitas Muhammadiyah MalangEmail : rasyidharun30@yahoo.co.idABSTRACTSoybeans grown in Indonesia generally is yellow-skinned varieties, while the black soybeans received less attention. In fact, black soybean varieties are superior to yellow varieties, both in terms of nutritional content. The results showed that (1) Plant height at harvest, seed weight per plant, number of branches, number of fertile nodes is determined jointly by the varieties, plant spacing and fertilizer P. (2) The weight of seeds per hectare, seed weight per hectare, the index , harvesting and crop seed yield percentage is determined jointly by the varieties with spacing. (3) Varieties Detam-1 with a spacing of 40 x 15 cm have the best seed production, ie 2430.94 kg / ha (2.4 tons / ha) . WhileCikurai varieties with a spacing of 40 x 30 cm has the lowest production. (4) The surface area of the seed seed, water absorbency seed, soybean seed coat thickness is determined jointly by the spacing of the fertilizer P. (5) The content of phosphorus is determined jointly by the varieties, plant spacing and fertilizer P. The glucose content determined shared between varieties and fertilizer P. (6) the fat content of each seed is determined by the variety and fertilizer P. the protein content is determined jointly by the varieties of seeds, plant spacing and fertilizer P. (7) variety Detam-1 with spacing of 40 x 30 cm and fertilizer P 162 kg / ha P2O5 has the best protein content compared with other combinations. (8) varieties Detam-1 has a production and seed quality is best, while Cikurai varieties have a low quality of seed production compared other varieties. (9) Improved plant spacing and fertilizer P will increase the production and quality of soybean seed.Keywords: Black soybean varieties, spacing, fertilizer P dosege, quality seeds Black Soybean VarietiesABSTRAKKedelai yang dibudidayakan di Indonesia umumnya adalah varietas berkulit kuning, sementara kedelai berkulit hitam kurang mendapat perhatian. Padahal, kedelai varietas hitam lebih unggul dibandingkan varietas kuning, baik dari sisi kandungan nutrisi. Hasil penelitian menunjukkan bahwa (1) Tinggi tanaman saat panen, berat biji per tanaman , jumlah cabang, jumlah buku subur ditentukan bersama oleh varietas, jarak tanam, dan dosis pupuk P. (2) Berat biji per hektar , berat benih per hektar,indeks, umur panen dan persentase rendemen benih panen ditentukan bersama oleh varietas dengan jarak tanam . (3) Varietas Detam-1 dengan jarak tanam 40 x 15 cm memiliki produksi benih yang terbaik, yaitu 2430,94 kg/ha (2,4 ton/ha).Sedangkan varietas Cikurai dengan jarak tanam 40 x 30 cm memiliki produksi terendah. (4) Luas permukaan benih benih, Daya serap air benih, tebal kulit benih kedelai ditentukan bersama oleh jarak tanam dengan dosis pupuk P. (5) Kandungan senyawa fosfor ditentukan bersama oleh varietas, jarak tanam, dan dosis pupuk P. Sedangkan kandungan glukosa ditentukan bersama antara varietas dan dosis pupuk P.(6) Kandungan lemak benih masing-masing ditentukan oleh varietas dan dosis pupuk P. Sedangkan kandungan protein benih ditentukan bersama oleh varietas, jarak tanam, dan dosis pupuk P.(7) Varietas Detam-1 dengan jarak tanam 40 x 30 cm dan dosis pupuk P 162 kg/ha P2O5 memiliki kandungan protein terbaik dibandingkan dengan kombinasi yang lain.(8) Varietas Detam-1 memiliki produksi dan mutu benih yang terbaik, Sedangkan varietas Cikurai memiliki produksi mutu benih yang rendah dibandingkan varietas lain.(9) Peningkatan jarak tanam dan dosis pupuk P akan meningkatkan produksi dan mutu benih kedelai.Kata Kunci : Varietas kedelai Hitam, Jarak tanam, Dosis pupuk P, Mutu benih Kedelai Varietas Hitam